MiR-26a-5p mediates TLR signaling pathway by targeting CTGF in LPS-induced alveolar macrophage. Issue 6 (4th June 2020) - Li, Chunyan; Han, Tingfeng; Li, Run; Fu, Liming; Yue, Lei
Abstract: To explore the regulation mechanism of miR-26a-5p and connective tissue growth factor (CTGF) in lipopolysaccharide (LPS)-induced alveolar macrophages, which is a severe pneumonia cell model. MH-S cells were grouped into Normal group, Model group, negative control (NC) group, miR-26a-5p mimic group, oe-CTGF group, miR-26a-5p mimic + oe-CTGF group. The expression level of miR-26a-5p, CTGF and Toll-like receptor (TLR) signaling related molecules (TLR2, TLR4 and nuclear factor-κB p65) were detected by qRT-PCR and WB, respectively. The cell viability and apoptosis rate were detected by methyl thiazolyl tetrazolium (MTT) and flow cytometry, respectively. Compared with the Normal group, the expression level of miR-26a-5p was significantly decreased, while CTGF protein level was significantly increased in the Model group. Compared with the Model group, MH-S cells with miR-26a-5p overexpression showed enhanced cell viability, decreased apoptosis rate, declined expression level of TLR signaling related molecules and reduced level of tumor necrosis factor-α (TNF-α), interleukin (IL) 6 (IL-6) and IL-1β, while those with CTGF overexpression had an opposite phenotype. In conclusion, miR-26a-5p can inhibit the expression of CTGF and mediate TLR signaling pathway to inhibit the cell apoptosis and reduce the expression of proinflammatory cytokines in alveolar macrophages which is a cell model of severe pneumonia.